Effectiveness of Top-Tier Information Technology Software Service Companies: A Multi-Component Perspective. Issue 2 (3rd April 2021) - Goyal, Sumit; Sah, Ash Narayan; Puri, Jolly
ABSTRACT: Information Technology (IT) firms are structured internally into various components to provide customized services to their customers. Owing to the significance of internal structure, the objective of the paper is to study quarterly efficiency of five IT software companies (Infosys, Tata Consultancy Services (TCS), Wipro, Cognizant and Accenture) based on components like FSI (Banking, Financial, Securities, and Insurance), MFG (Manufacturing), RCL (Retail, Consumer Packaged Goods, and Logistics), ERU (Energy, Utilities and Resources), CME (Communication, Media, and Entertainment) and LSH (Life Sciences and Health Care Services) using multi-component data envelopment analysis. Results obtained establish that Infosys is the most efficient company followed by Cognizant and Accenture while TCS and Wipro are inefficient in some of the components. Empirical results show that the companies performed efficiently in FSI, RCL and CME components whereas ERU, LSH and MFG components require improvement. Further, the geography-wise efficiency trends indicate that the selected companies are more efficient in the rest of the world as compared to the European and North American regions. These findings will help IT firms in identifying their inefficient components and provide guidance in formulating strategies for improvements. Moreover, other domestic and foreign firms may also learn from the findings of the study.